2013
DOI: 10.15288/jsad.2013.74.867
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, Variation in the Cannabinoid Receptor (CNR1) and Fatty Acid Amide Hydrolase (FAAH) Genes, and Marijuana-Related Problems

Abstract: Impulsivity is associated with increased marijuana use and subsequent marijuana-related problems among marijuana users. In addition, single nucleotide polymorphisms (SNPs) in the cannabinoid receptor 1 (CNR1) and fatty acid amide hydrolase (FAAH) genes have been associated with cannabis-related phenotypes. This exploratory study tested whether the association between different aspects of impulsivity and the number of marijuana-related problems among users is explicated by variation in these putative cannabinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 57 publications
2
31
1
Order By: Relevance
“…Cannabis users were required not to use cannabis for 12 hours (overnight) prior to scanning (same requirement for nicotine smoking). PET intake assessments included 1) A breath alcohol concentration (BAC) measurement to ensure abstinence from alcohol (BAC=0 required for scanning); 2) A urine toxicology to rule out medication and illicit drug use (other than cannabis in cannabis users); 3) Urine pregnancy test (female subjects only); 4) Expired carbon monoxide (CO <10 ppm to rule out recent tobacco or cannabis smoking); 5) Craving and withdrawal questionnaires for cannabis users only [Severity of Dependence Scale (SDS), Obsessive Compulsive Smoking Scale (OCSS), Marijuana Craving Questionnaire-Short Form (MCQ) (52), and Marijuana Withdrawal Checklist (MWC) (53)] and the Time Line Follow Back to assess cannabis use over previous 90 days (54); and 6) the Barratt Impulsiveness Scale (BIS) to measure trait impulsivity that has been related to eCS and greater cannabis related problems in cannabis users (as a moderator of this relationship) (55, 56). …”
Section: Methodsmentioning
confidence: 99%
“…Cannabis users were required not to use cannabis for 12 hours (overnight) prior to scanning (same requirement for nicotine smoking). PET intake assessments included 1) A breath alcohol concentration (BAC) measurement to ensure abstinence from alcohol (BAC=0 required for scanning); 2) A urine toxicology to rule out medication and illicit drug use (other than cannabis in cannabis users); 3) Urine pregnancy test (female subjects only); 4) Expired carbon monoxide (CO <10 ppm to rule out recent tobacco or cannabis smoking); 5) Craving and withdrawal questionnaires for cannabis users only [Severity of Dependence Scale (SDS), Obsessive Compulsive Smoking Scale (OCSS), Marijuana Craving Questionnaire-Short Form (MCQ) (52), and Marijuana Withdrawal Checklist (MWC) (53)] and the Time Line Follow Back to assess cannabis use over previous 90 days (54); and 6) the Barratt Impulsiveness Scale (BIS) to measure trait impulsivity that has been related to eCS and greater cannabis related problems in cannabis users (as a moderator of this relationship) (55, 56). …”
Section: Methodsmentioning
confidence: 99%
“…Thus far, studies have linked the CNR1 G allele with reduced bilateral hippocampal volumes (Schacht et al, 2012) and increased cannabis cue-reactivity in PFC-cingulate regions (Filbey et al, 2009), C allele with increased trait anxiety (Bidwell et al, 2013), withdrawal and negative affect following abstinence (Haughey et al, 2008), and increased craving following cannabis cues (Haughey et al, 2008) in young adult cannabis users. No links between CNR1 genotype and behavioral problems, impulsivity (Bidwell et al, 2013) or amygdala volumes (Schacht et al, 2012) have been found. Cannabis-using carriers of the FAAH C allele have demonstrated greater PFC, cingulate and nucleus accumbens activation (Filbey et al, 2009) and increased withdrawal (Schacht et al, 2009) and craving (Haughey et al, 2008) symptoms following cannabis cue exposure.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
“…FAAH C allele carriers also demonstrated greater withdrawal and negative affect following abstinence (Haughey et al, 2008). Results thus far have found no link between FAAH genotype and trait anxiety, impulsivity or behavioral problems (Bidwell et al, 2013). In summary, these preliminary studies suggest that genetics, especially those related to reduced endogenous cannabinoid signaling such as the FAAH C allele, may place subgroups at greater risk for increased CUD severity and more severe neurocognitive consequences of cannabis exposure.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
“…In addition, the A allele produces a defective mutant enzyme with reduced expression and stability (Chiang et al, 2004). Only one study investigated the effect of rs4141964 in SU; in a multi-ethnic study, Bidwell and colleagues (2013) found a significant main effect of a FAAH haplotype containing the minor alleles of rs4141964 and rs324420 that predicted higher marijuana-related problems. Thus, our results concur with the current literature and suggest that the minor alleles of rs4141964 and rs324420 are associated with CUDs.…”
Section: Discussionmentioning
confidence: 99%